Recharging China in War and Revolution, 1882-1955 - Tan, Ying Jia, 1978- (Book collections on Project MUSE., 2021)
"The formative years of China's electrical industries between 1882 and 1955 overlapped with a period of incessant warfare and revolutionary upheaval. The electrification of textile manufacturing, wartime electrical infrastructure build-up, and the battles for control over electrical power production and consumption, reveal the inter-connectedness between energy security and national survival"--